A High-Sensitivity Radar System Featuring Low Weight and Power Consumption - Mann, Sebastian; Lurz, Fabian; Weigel, Robert; Kölpin, Alexander (IEEE Microwave Magazine, 2015)
In this article, a lightweight, low-power radar system for vibration monitoring has been presented. Based on a theoretical analysis of the competition scenario, an optimized system concept has been developed. The radar front end is able to sequentially evaluate the in-phase and quadrature component of the received signal with only a single hybrid coupler and power detector, reducing the overall weight to 5 g including the power-supply cable. A low duty cycle of 1% allowed the power to average 1.5 mW. As the minimum required sensitivity was limited to 0.5-mm oscillation amplitude, the most challenging parts in this student competition were, in our opinion, the tight power and weight optimizations. As the competition required only vibration detection butno ranging, a minimalistic system concept optimized for this application was proposed. The system features a free-running VCO sourced directly from the power supply without any further stabilization. For ranging applications, temperature changes as well as supply and tuning voltage variations at the VCO could have a severe impact on the system's accuracy. However, for pure vibration detection of a well-defined target, this is not a problem. Further improvements could be achieved when designing a customized 24-GHz oscillator, optimized for high efficiency [9] and fast turn-on time. In addition, the necessary number of measurements per second could be further investigated. Currently, with ten measurements per second, there is a convenient safety margin against false detections; however, fewer measurements would directly reduce the duty cycle and thus the average power consumption of the system.
elib2cris::1512001600,mann2015a
Keywords: Low Power; Radar